2021
DOI: 10.3390/ijerph18157774
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Regulations and Corporate Green Innovation in China: The Role of City Leaders’ Promotion Pressure

Abstract: China and other emerging market countries have suffered from the problem of environmental pollution while developing rapidly in the past few decades. In recent years, many countries have introduced strict environmental regulations in order to achieve sustainable development. This paper discusses the relationship between environmental regulations and corporate green innovation from the perspective of regional leaders’ promotion pressure. The empirical results show that direct policy regulation within the region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 77 publications
0
31
0
Order By: Relevance
“…It provides detailed information of each listed firm’s financial, operating and corporate governance information, among others. This database has been widely used in previous studies regarding Chinese listed firms’ green innovation performance [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides detailed information of each listed firm’s financial, operating and corporate governance information, among others. This database has been widely used in previous studies regarding Chinese listed firms’ green innovation performance [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Following previous studies [ 26 , 27 ], we control a comprehensive set of variables that may affect the green innovation performance.…”
Section: Methodsmentioning
confidence: 99%
“…Sen (2015) [16] took the automotive industry in a transnational environment as the research object and studied the relationship between environmental regulation and technological innovation, and discovered that environmental regulation can not only improve the level of technological innovation, but also reduce environmental pollution. Yang et al (2021) [17] found that the strength of environmental regulation was positively related to firms' green innovation. Moreover, Calel (2011) [18], Bréchet and Meunier (2014) [19] believe that there is a non-linear relationship between environmental regulations and the degree of green technology innovation.…”
Section: Environmental Regulation and Green Innovationmentioning
confidence: 99%
“…However, since economic growth was placed in the primary position and the competition among local cadres was based on the economic performance, local governments tend to generally enforce environmental regulations with low standards to obtain mobility, which leads to extensive development at the expense of environmental pollution [17]. In particular, due to the characteristics of spatial spillover effect and regional heterogeneity for air pollution, the win of "blue sky defense war" still has a long way to go [18].…”
Section: A Brief Description Of Institutional Backgroundmentioning
confidence: 99%
“…To vividly illustrate two different types of promotion logic, we draw Figure 1 as follows. In the past, the traditional guiding ideology of a political promotion tournament was "only GDP", that is, local cadres with better economic performance are more likely to be promoted while the opposite will face a lower promotion probability [16][17][18]. Since the announcement of ecological civilization, a new model of political promotion tournament was proposed and air pollution reduction (or environmental performance) had priority over economic growth, that is, only those who meet the environmental criteria firstly and achieve rapid economic growth simultaneously are more likely to be promoted [19][20][21][22][23].…”
Section: A Brief Description Of Institutional Backgroundmentioning
confidence: 99%